2016
DOI: 10.1016/j.atherosclerosis.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

High shear stress relates to intraplaque haemorrhage in asymptomatic carotid plaques

Abstract: Higher maximum shear stress is associated with intraplaque haemorrhage and calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 42 publications
5
76
0
Order By: Relevance
“…Previous studies have shown that the intensity of neovasculature within plaques and the blood pressure were associated with carotid IPH. Beyond these risk factors, investigators demonstrated that local mechanical conditions may play important role in the occurrence of carotid IPH . In contrast, the normal vessel wall of intracranial arteries is lacking of vasa vasorum and the local hemodynamics are complex which may be different from the extracranial carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the intensity of neovasculature within plaques and the blood pressure were associated with carotid IPH. Beyond these risk factors, investigators demonstrated that local mechanical conditions may play important role in the occurrence of carotid IPH . In contrast, the normal vessel wall of intracranial arteries is lacking of vasa vasorum and the local hemodynamics are complex which may be different from the extracranial carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In the carotid circulation, ulceration of carotid plaques, visible on angiography or on pathological examination, was seen most often in regions where WSS was highest [43] and the inflammatory burden was severe [44]. In line with the experimental and autopsy studies, longitudinal and cross-sectional human coronary and carotid studies have shown an increase in plaque necrotic core, calcium [35], and strain [45], development of expansive remodeling [35,46], presence of IPH [47], large necrotic core [34,46,48], a necrotic core in contact with the lumen [48], and napkin-ring sign [46] in areas exposed to high WSS. Meanwhile, some data show that WSS might not have the same role in development of plaque erosion as it has in the development of plaque rupture [9,10].…”
Section: High Wall Shear Stressmentioning
confidence: 97%
“…High WSS at baseline was associated with subsequent ulceration at follow-up imaging. The relationship between WSS and IPH was further explored in a relatively large cross-sectional study in 93 carotid arteries of 74 asymptomatic participants from the Rotterdam Study who underwent magnetic resonance imaging for CFD simulations and plaque composition assessment [47]. The investigators found a relationship between higher maximum WSS and the presence of IPH and calcification, independent of plaque thickness, age, and sex.…”
Section: High Wss and Individual Characteristics Of High-risk Plaquementioning
confidence: 99%
“…At the shoulder area, however, stresses increase considerably attributed to blood incompressibility. Thus, not only are ROS production and inflammation stimulated in the underlying tissue (as a result of high, rather than low, stresses in this area), but an abrupt transition between mildly and highly stressed areas occurs, favoring plaque rupture and neovessel formation and rupture . Similarly, at the downstream shoulder, flow turbulence leads to decrease of transmural pressure attributed to vortex‐formation–related energy dissipation, mirroring the events of the upstream region.…”
Section: On the Genesis Of Atherosclerotic Plaquementioning
confidence: 99%